The mean and peak physical demands during transitional play and high pressure activities in elite football - Bortnik, L.; Burger, J.; Rhodes, D. (Biology of Sport, 2022)
The aim of the present study was to establish the effect of transitional activities (TA) on physical metrics. Global Positioning System technology was utilized on 23 elite outfield footballers over 10 games to quantify absolute metrics per minute such as total distance (TD; m · min-1), sprint distance (SD; m · min-1), the number of high-intensity accelerations and decelerations (A+D; n · min-1), and high-speed running distance (HSRD; m · min-1). TD - total distance; HSRD - high-speed running distance; SD - sprint distance and highintensity acceleration distance (Acc B3 Dist) were also quantified. Metrics were observed in relation to 4 TA`s commonly observed in football matches. Positive Transitions (PT), Negative Transitions (NT), Fast Attacks (FA) and High Pressure Activities (HP). Main effects for transition and game were observed. Comparisons were also made between 90 minute averages and transitional mean scores. NT displayed the highest TD (m · min-1) when compared to other TA`s (p = 0.05). Observation of SD (m · min-1) for all transitions highlighted higher outputs when in PT (p = 0.05). HP TA displayed the lowest output in all metrics (p = 0.05), except high-intensity accelerations and decelerations A+D (n · min-1). The mean average and peak average outputs for TA and 90min average detailed elevated physical outputs across all metrics. Absolute physical metrics are increased when observing transitional play, representing the maximum physical exposure that athletes experience in games. This knowledge should be utilized when implementing high-velocity exposures within a weekly microcycle, to best prepare players for match play.